1997
DOI: 10.1007/s004390050354
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of the type-I 15-PGDH gene to 4q34-q35

Abstract: The gene encoding the human NAD(+)-dependent 15-hydroxyprostaglandin dehydrogenase, designated type-I 15-PGDH, was mapped to chromosome 4 by analyzing its segregation in a panel of human-hamster somatic cell hybrids. This gene was further localized to bands 4q34-q35 by in situ hybridization on human chromosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The mouse gene is 11.3 kb in length [29], whereas the human gene is 31 kb [30]. The human gene is localized to 4q34-q35 [31]. Both mouse and human genes contain seven exons and 6 introns.…”
Section: Introductionmentioning
confidence: 99%
“…The mouse gene is 11.3 kb in length [29], whereas the human gene is 31 kb [30]. The human gene is localized to 4q34-q35 [31]. Both mouse and human genes contain seven exons and 6 introns.…”
Section: Introductionmentioning
confidence: 99%
“…The key enzyme responsible for metabolic inactivation of prostaglandins, including PGE 2 , is NAD ϩ -dependent 15-hydroxyprostaglandin dehydrogenase (15-PGDH) (38). The human gene is located on chromosome 4 and codes for a 29-kDa enzyme that catalyzes the formation of 15-ketoprostaglandins (30,38). 15-Ketoprostaglandins possess greatly reduced biological activities.…”
mentioning
confidence: 99%
“…It has been proposed that two major steps are involved in prostaglandin inactivation: uptake from the plasma membrane by prostaglandin transporters and oxidation by NAD ϩ -dependent 15-hydroxyprostaglandin dehydrogenase (15-PGDH) (21,22,34). Pichaud et al (24) noted that 15-PGDH is the main enzyme of prostaglandin degradation. By catalyzing the conversion of the 15-hydroxyl group of prostaglandins into a keto group, this ubiquitous enzyme strongly reduces the biological activity of these molecules (24).…”
Section: Prostaglandins (Pgs)mentioning
confidence: 99%
“…Pichaud et al (24) noted that 15-PGDH is the main enzyme of prostaglandin degradation. By catalyzing the conversion of the 15-hydroxyl group of prostaglandins into a keto group, this ubiquitous enzyme strongly reduces the biological activity of these molecules (24). Previous reports have shown that 15-PGDH was expressed in the proximal tubule, cortical, and outer medullary thick ascending limb, and collecting duct of the kidney but not in the macula densa or papilla (41).…”
Section: Prostaglandins (Pgs)mentioning
confidence: 99%